2021
DOI: 10.1097/mph.0000000000002173
|View full text |Cite
|
Sign up to set email alerts
|

Association Between SHMT1 rs1979277 Polymorphism and Risk of Acute Lymphoblastic Leukemia: A Systematic Review and Meta-analysis

Abstract: Objectives: The aim of this study was to explore the potential association the cytosolic serine hydroxy methyltransferase (SHMT1) rs1979277 polymorphism and the risk of acute lymphoblastic leukemia (ALL).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…55 This change could result in leucineto-phenylalanine amino acid substitution in SHMT1. 55 The SHMT1 C1420T polymorphism can decrease enzyme activity and lead to a reduction in folate levels, Hcy remethylation and DNA synthesis. 56 Studies have shown that SHMT1 1420CT/TT could decrease the risk of acute lymphocytic leukaemia.…”
Section: Serine Hydroxymethyltransferasementioning
confidence: 99%
See 2 more Smart Citations
“…55 This change could result in leucineto-phenylalanine amino acid substitution in SHMT1. 55 The SHMT1 C1420T polymorphism can decrease enzyme activity and lead to a reduction in folate levels, Hcy remethylation and DNA synthesis. 56 Studies have shown that SHMT1 1420CT/TT could decrease the risk of acute lymphocytic leukaemia.…”
Section: Serine Hydroxymethyltransferasementioning
confidence: 99%
“…A common single‐nucleotide polymorphism, cytosine (C) to thymus pyrimidine (T), occurs at nucleotide 1420 of the SHMT1 gene (C1420T, rs1979277) 55 . This change could result in leucine‐to‐phenylalanine amino acid substitution in SHMT1 55 . The SHMT1 C1420T polymorphism can decrease enzyme activity and lead to a reduction in folate levels, Hcy re‐methylation and DNA synthesis 56 .…”
Section: Application Of 1c Metabolism In Cancer Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that abnormal expression of SHMT1/2 may affect the occurrence and development of HCC by preventing proliferation and migration (13)(14)(15)(16). Although SHMT1 was identi ed as a susceptibility gene for a variety of malignant tumors via genome-wide association analysis (18)(19)(20)(21)(22)(23), the relationship between SHMT1/2 gene polymorphism and HCC susceptibility has not yet been clari ed. Therefore, it is necessary to conduct studies on the association between SHMT1/2 gene polymorphism and HCC susceptibility, which will help to provide an excellent foundation for the researches on the underlying mechanism of SHMT1/2 in HCC susceptibility.…”
Section: Introductionmentioning
confidence: 99%